Effect of Pitch Thread Combination of Dental Implant on Fatigue Safety and Life Performance - Danang Yudistiro; Yung-Chang Cheng (LPPM Universitas Duta Bangsa Surakarta, 2021)
During the implant procedure, one factor determining the surgery's success is the dental implant's stability. The stability index includes fatigue safety and life performance. A dental implant's thread pitch has been regarded as the essential factor for fatigue safety in many studies. However, the effect of the mixed thread pitch on fatigue safety and life performance are rarely investigated. Therefore, this study examines the impact of thread pitch on implants on the fatigue safety factor and dental implants' life. Four types of implants were studied: (0.5mm Pitch, 0.8mm Pitch, Combination Pitch (0.8mm with upper 0.5mm and 0.8mm with lower 0.5 mm). The material of a dental implant used in this study is Ti6al4v. According to ISO standard 14801, the fatigue safety factor is presented and compared using ANSYS/Workbench software. The results show that the combination pitch (0.8mm with upper Pitch 0.5 mm) has the highest life and safety factors.